(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ABSTRACT: This cross-disciplinary study seeks to investigate interviewers’ practices and perceptions during the faculty-hiring interview for an EFL assistant professor/ lecturer position. Data is collected through ethnographic notes, a questionnaire with the members of the hiring committees, and the analysis of official HR documents. Results revealed that current practices during faculty hiring interviews are somewhat an amorphous process namely in terms of procedures to conduct and evaluate interviews. Thus, stakeholders in higher education institutions should reconsider selection criteria for more validity of the job interview KEYWORDS: faculty hiring committee; job interview; anchored rating scale; interviewers’ perceptions; faculty position, EFL assistant lecturer ملخص تسعى هذه الدراسة إلى التحقيق في ممارسات أعضاء لجنة المحاورة وتصوراتهم خلال مقابلة توظيف الأساتذة المساعدين في قسم اللغة الإنجليزية . تم جمع البيانات من خلال الملاحظات ، واستبيان مع أعضاء لجان التوظيف ، وتحليل وثائق الموارد البشرية الرسمية.كشفت النتائج أن الممارسات الحالية أثناء مقابلات التوظيف هي عملية غير متبلورة إلى حد ما من حيث طريقة إجراء وتقييم المقابلات. وبالتالي ، يجب على أصحاب المصلحة في مؤسسات التعليم العالي إعادة النظر في معايير الاختيار لمزيد من صلاحية مقابلة العمل. كلمات مفتاحية: مقابلة العمل، أعضاء لجنة المحاورة ، توظيف الأساتذة المساعدين ، مقابلات التوظيف ، تقييم المقابلات.